Household survey on prevalence and risk factors for obesity in owned cats from Central Brazil - Danilo Conrado Silva; Mariana Yukari Hayasaki Porsani; Aparecido Divino da Cruz; Erika Figueiredo Pereira; Klayto José Gonçalves dos Santos; Lysa Bernardes Minasi; Vitória Alvarenga Nunes; Alex Silva da Cruz; Fabio Alves Teixeira (PLoS ONE, 2026)
Few studies have conducted the prevalence of obesity in cat populations and the associated risk factors by assessing cats in their homes, regardless of whether they had visited a veterinary hospital. Moreover, such studies are scarce in Latin America, and, to date, few census-based, in-home epidemiological assessment of feline obesity has been conducted in Brazil. This study aimed to estimate the prevalence of obesity in owned cats in the metropolis of Goiânia, Goiás, Brazil, and to assess the presence of risk factors related to the animals, their owners, the home environment, and cat management practices. A cross-sectional study was conducted with 188 cats and their owners, using geographically stratified household sampling. The animals were categorized based on body condition score (BCS) as underweight, ideal weight, overweight, or obese, and prevalence rates were calculated. The BCS was investigated for its association with animal, owner, environmental, and management characteristics using the Kruskal-Wallis test (α = 5%). Subsequently, characteristics with p ≤ 0.05 were analyzed as potential risk factors for overweight or obesity using binary logistic regression. Kappa analysis was used to determine the agreement between the BCS determined by veterinarians and the owners’ perception of their cats’ body condition. The prevalence of overweight and obesity in cats was 28.7%. Factors related to age and activity level, type of household, as well as the owners’ education and occupation, were identified as risk factors for the development of overweight or obesity in the study cat population. Additionally, protective factors against overweight and obesity were identified, including the number of cats in the household, the location of the household, and the owners’ perception of their own diet. The agreement between the actual BCS of the animals and the owners’ perception of their cats’ body condition was considered low.